BONE IS NOT JUST CALCIUM AND VITAMIN DA REVIEW OF ESSENTIAL NUTRIENTS REQUIRED FOR BONE HEALTH - admin pjmd; Sana Lodhi; Saeeda Baig; Danial Arshad (ziauddin University, 2024)
Bone formation is a constant procedure in which osteoblasts lay new bone and osteoclasts resorb it. Mineralization takes place at active bone formation sites where the extracellular matrix vesicles, the major sites of apatite mineral deposition, are present. Turnover of bone, which maintains its structure and integrity, has several events such as activation, resorption and osteogenesis by osteoblasts. The bone crystals proliferation depends on the presence of collagen, hormones, minerals and vitamins such as phosphorus, magnesium, calcium, zinc, fluoride, potassium, manganese, boron, copper, iron, calcium and a number of vitamins such as B,K,C,A,D, etc. Information regarding the elements involved in bone formation was retrieved through studies published up to 2017 in PubMed, Medline and other authentic search engines available in the University. This review highlights the individual roles of specific vitamins and minerals at the respective steps of bone formation, insufficiency at all particular stages result in various bone pathologies, leading to deficiency disorders, fractures and poor friable bones. Since the role of vitamin D and calcium is well established therefore these were not included in this review.